The Beginning of More Worries: Doctoral Candidates’ Untold Stories After Submission of Dissertation - Waheed, Syed Abdul; Gilani, Nadia; Raza, Mehwish; Ahmad, Farooq (Frontiers in Psychology, 2021)
Most of the doctoral candidates are deeply engaged in the timely completion of their dissertations during the research process. Nevertheless, during and after submitting their dissertations, they experience many procedural barriers and delays in the submission and external evaluation of the dissertation. The present study focused on this particular situation in which doctoral candidates become anxious, impatient, and disappointed while experiencing a prolonged delay in processing their dissertation during and after the submission. The researchers tend to explore doctoral candidates’ storied experiences they had while confronting such procedural barriers and delays. We undertook a narrative mode of inquiry to explore the events and storied experiences through interviewing doctoral candidates from public universities in the province of Punjab, Pakistan. Nine doctoral candidates were selected through snowball sampling with the criterion of including those participants who were waiting for their external reviews at least for more than one year. From the narratives, the emergent themes include jealousy among supervisors, the pressure of paper publication, lack of administrative support, external evaluation and follow-up and stress of delayed evaluation. The study has implications for relaxing procedural formalities during and after submission of a doctoral dissertation to facilitate students in the timely attainment of their doctoral degrees.